2016
DOI: 10.1002/glia.23074
|View full text |Cite
|
Sign up to set email alerts
|

Microglia contributes to plaque growth by cell death due to uptake of amyloid β in the brain of Alzheimer's disease mouse model

Abstract: Pathological hallmarks of Alzheimer's disease (AD) include extracellularly accumulated amyloid β (Aβ) plaques and intracellular neurofibrillary tangles in the brain. Activated microglia, brain-resident macrophages, are also found surrounding Aβ plaques. The study of the brain of AD mouse models revealed that Aβ plaque formation is completed by the consolidation of newly generated plaque clusters in vicinity of existed plaques. However, the dynamics of Aβ plaque formation, growth and the mechanisms by which mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
128
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 62 publications
13
128
0
3
Order By: Relevance
“…Similarly, a two‐photon in vivo study indicated that microglial uptake of aggregated Aβ, followed by microglial death and release of residual Aβ, could lead to the spreading of amyloid deposition (Baik et al . ).…”
Section: The Relationship Of Microglia and Aβ Plaque Depositionmentioning
confidence: 97%
“…Similarly, a two‐photon in vivo study indicated that microglial uptake of aggregated Aβ, followed by microglial death and release of residual Aβ, could lead to the spreading of amyloid deposition (Baik et al . ).…”
Section: The Relationship Of Microglia and Aβ Plaque Depositionmentioning
confidence: 97%
“…To overcome the limitations of these markers, lineage tracing mouse models have been generated using the microglial expression of the fractalkine receptor, Cx3cr1 (Jung et al, ). One study crossbred the Cx3cr1 GFP/GFP mice with the 5xFAD mouse model of AD and found that dying GFP positive cells contributed to Aβ plaque growth by releasing previously phagocytosed Aβ into the extracellular space (Baik, Kang, Son, & Mook Jung, ). However, macrophages can also express Cx3cr1, thus the contribution of peripheral monocyte‐derived macrophages cannot be ruled out.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a neurodegenerative disorder characterized by extracellular deposits of amyloid‐β (Aβ) peptides, intracellular neurofibrillary tangles, and chronic neuroinflammation resulting in a progressive loss of memory and cognitive function (Prinz & Priller, ). While Aβ can be cleared by resident microglia and astrocytes (Baik et al, ; Ries & Sastre, ), these cells become unable to clear Aβ pathology as animals age. The peripheral immune system is clearly implicated in AD pathogenesis (Heneka et al, ; Prinz & Priller, ).…”
Section: Introductionmentioning
confidence: 99%